2016
DOI: 10.1074/jbc.m115.705095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serine 129 Phosphorylation on α-Synuclein Aggregation, Membrane Association, and Internalization

Abstract: Although trace levels of phosphorylated ␣-synuclein (␣-syn) are detectable in normal brains, nearly all ␣-syn accumulated within Lewy bodies in Parkinson disease brains is phosphorylated on serine 129 (Ser-129). The role of the phosphoserine residue and its effects on ␣-syn structure, function, and intracellular accumulation are poorly understood. Here, co-expression of ␣-syn and polo-like kinase 2 (PLK2), a kinase that targets Ser-129, was used to generate phosphorylated ␣-syn for biophysical and biological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 79 publications
5
99
0
5
Order By: Relevance
“…Other pathogenic species, particularly oligomers, have also been postulated to directly permeabilize membranes or form membrane-spanning pores (43)(44)(45). It has recently been demonstrated that phosphorylation of exogenous ␣-syn species leads to an increase in lysosomal rupture following endocytosis, which may be a relevant mechanism of pathological ␣-syn transmission (46). Using sonicated pffs generated from unmodified recombinant ␣-syn, we did not observe endocytosis-independent mechanisms of uptake in our studies.…”
Section: Discussionmentioning
confidence: 41%
“…Other pathogenic species, particularly oligomers, have also been postulated to directly permeabilize membranes or form membrane-spanning pores (43)(44)(45). It has recently been demonstrated that phosphorylation of exogenous ␣-syn species leads to an increase in lysosomal rupture following endocytosis, which may be a relevant mechanism of pathological ␣-syn transmission (46). Using sonicated pffs generated from unmodified recombinant ␣-syn, we did not observe endocytosis-independent mechanisms of uptake in our studies.…”
Section: Discussionmentioning
confidence: 41%
“…While Engelborghs et al found that on the strength of polo-like kinase 2 to target Ser129 specifically, pS129 exhibit no influence on fibrillization kinetics of α-Syn16. Recently, co-expression of α-Syn with polo-like kinase 2 in E. coli , was used to prepare pS129 α-Syn, with resulting earlier fibril formation of pS129 α-Syn compared to WT α-Syn17. The inconsistency of the outcome may partially result from the S87A mutation and the efficiency of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The main component of the pathological lesions is extensively phosphorylated α-Syn at serine 129 (pS129 α-Syn)14, and pS129 α-Syn may play a critical role in synucleinopathy pathogenesis. Phosphorylation at Ser129 can regulate α-Syn fibril formation14151617 and enhance α-Syn toxicity both in vitro and in vivo 18192021. As the main form of α-Syn in the pathological process, pS129 α-Syn may be associated with multiple strain formation in vivo .…”
mentioning
confidence: 99%
“…We hypothesized that this may reflect the subpopulation of AD subjects with concomitant LB pathology, and found that the mismatch (α-syn–p-tau 181 -Mis) between these two markers both correlated with worse cognitive outcomes, and improved the association of the t-tau/Aβ 42 ratio with these measures when included in the model [17]. Importantly, most α-syn present in LBs is highly phosphorylated, especially at serine 129 (pS129) [15, 2022], which is thought to alter aggregation and toxicity of α-syn[23, 24]. Notably, the CSF pS129 was significantly higher in PD patients than in healthy controls, and correlated with PD severity[16, 25], suggesting it may serve as a marker of PD pathology independently of total α-syn, which tends to be lower in the CSF of PD patients[18, 2629].…”
Section: Introductionmentioning
confidence: 99%